Pengaruh Latihan Target Terhadap Ketepatan Smash Bulutangkis pada Mahasiswa UM Palopo - Ahmad Syarif Burhan; Nasruddin Nasruddin; Junalia Muhammad (Universitas Hamzanwadi, 2026)
This study was motivated by the low accuracy of badminton smashes among students in the Badminton Club at Muhammadiyah University of Palopo, where many smashes went out of bounds, missed the target, or were easily returned by opponents because the training provided emphasized hitting power over the accuracy of shuttlecock placement. The study aimed to determine the effect of target practice on the accuracy of badminton smashes among UM Palopo students. The method used was an experiment with a one-group pretest-posttest design. The population consisted of 20 students from the University of Muhammadiyah Palopo Badminton Club, selected using total sampling. The target practice intervention was conducted over 16 sessions using a badminton smash accuracy test as the measurement instrument, and the data were analyzed using a paired-sample t-test. The results showed that the mean pretest score of 36.80 increased to 43.85 on the posttest, representing an increase of 7.05 points (19.16%). The paired-sample t-test yielded a calculated t-value of 31.570 > the critical t-value of 2.085 and a p-value of 0.000 < 0.05, with a Cohen’s d effect size of 2.44, classified as very large. In conclusion, targeted practice had a significant effect on improving the accuracy of badminton smashes among UM Palopo students and is recommended as an effective training method for enhancing smash skills.